Development of a descriptive study of work stress, physical activity, eating habits and obesity in the maquiladora industry using software applications - Armenta Hernandez, Oziely Daniela; Maldonado-Macías, Aide Aracely; Hernandez Arellano, Juan Luis; Baez López, Yolanda (2020)
Workers around the world face major changes in work organization and industrial relations to fulfill the demands of modern working life. The problem of work stress and obesity have become rather delicate subjects because of the negative consequences it brings for employees and companies. The objectives of this research perform a descriptive analysis using the SPSS v.23 software on work stress, physical activity, eating habits and obesity in the industry for sample characterization. Methods entail the application of a questionnaire for gathering information, the creation of the database in the software and the accomplishment of the descriptive analysis of each section of the questionnaire with the help of the software. As results, physical activity is that all three dimensions show the degree of sedentariness as values fall below 9. As for the diagnosis of eating habits, from the resulting scores, the population shows a diagnosis of food anxiety since all the dimensions of the instrument were among the mean values obtained. As conclusions, manufacturing industries must take preventive actions to reduce them by increasing physical activity and improving eating habits among staff. It is also recommended to implement techniques to improve health, ergonomics and safety practices in the manufacturing industry, so it is that